ANALYSIS OF THE IMPLEMENTATION OF E-COMMERCE AND PRODUCT INNOVATION IN INCREASING THE INCOME OF EUFORIA GARMENT MSMES IN SIDOKUMPUL VILLAGE - Hariyanto, Widia Eka; Anwar, Chairil; Muzakki, Kafidin; Fahriani, Dian (Universitas Muhammadiyah Bengkulu, 2025)
MSMES Euforia Garment is a screen-printing t-shirt business that is facing challenges in increasing revenue in the digital era. The purpose of this research is to determine how MSMES Euforia Garment can increase its revenue through the application of e-commerce and product innovation, with a case study on MSMES Euforia Garment. This research uses a qualitative approach, where data is collected through observation, interviews, and documentation. The research results show that since the utilization of e-commerce from 2020 to 2022, there has been an impact on revenue increase with respective growths of 15.90% (2020), 42.47% (2021), 69.09% (2022), 95.70% (2023), and 126% (2024). Meanwhile, product innovation, which was implemented maximally and consistently starting in 2021, has had an impact on revenue increase with growths of 21.48% (2021), 44.18% (2022), 54.04% (2023), and 65.11% (2024). It can be concluded that the implementation of e-commerce and product innovation has increased the revenue of MSMES Euforia Garment, but it is necessary to expand the platform and develop product innovation to be more optimal. As a solution, MSMEs are advised to expand the use of e-commerce to other platforms such as Lazada and Tokopedia